Failure of Biologic Therapy in Psoriasis - Cardona, Rocío; Pelet del Toro, Natalia M.; Michelen-Gómez, Eduardo; Arias-Berrios, Gabriel E.; Martín-García, Rafael F. (Puerto Rico Health Sciences Journal, 2021)
Objective: This study aims to describe the frequency of biologic therapy failure in psoriasis patients along with associated patient demographics and characteristics. Methods: This was a retrospective medical-record review of psoriasis patients evaluated from January 1st, 2013, through May 1st, 2018, and who failed at least once to adhere to their biologic therapy. Results: Seventy-seven patients with psoriasis who had discontinued biologic therapy at least once were included in this study. Hypertension (58.4%), diabetes (37.7%), dyslipidemia (27.3%), and psoriatic arthritis (23.4%) were the main comorbidities observed. Adalimumab (ADA, 80.5%), ustekinumab (UST, 70.1%), and etanercept (ETA, 14.2%) were the most frequently used biologics in our cohort. The biologic with the longest mean duration of use prior to its discontinuation was UST (17.0 months), followed by ADA (15.9 months) and ETA (13.6 months). Conclusion: The most common reason for discontinuing biologic therapy was that said therapy was not effective, though for ETA and UST, the fact that biologic therapies are not universally covered by insurance company was found to be associated with their discontinuation, as well. There were no statistically significant associations found between biologic therapy discontinuation and age, gender, or comorbidities, which last included obesity, class I. Larger studies are warranted to identify risk factors associated with biologic therapy failure to help guide drug selection, decrease morbidity associated with such nonadherence and improve patient outcomes.